“TELANG TEA TIME”, MINUMAN SEHAT PENANGKAL HIPERTENSI - Prodyanatasari, Arshy; Pratiwi, Wahyu Nur; Christanti, Sherly Herdiana; Novitasari, Debby; Santoso, Natasya Tian Harum; Hardianti, Berliana Putri; Hidayat, Muhammad Syam (Universitas Sanata Dharma, 2024)
Hypertension is characterized by blood pressure above 140/90 mmHg and is an alarm of hemodynamic imbalance in the body. Hypertension is a silent killer. One of the efforts that can be made to stabilize blood pressure is by consuming telang (Clitoria ternatea L.) flower herbal drinks. The high antioxidant content in telang flowers is beneficial for health. To introduce the benefits of flowers to the community, community service activities were carried out in Tunge Village, Kediri Regency. This community service was carried out using the Participatory Action Research (PAR) method with a total of 238 participants. The community service was carried out in July-August 2024. It was divided into three activity groups. In each implementation, the activity was divided into six stages, namely: health screening, pretest, hypertension education, demonstration of making telang flower tea, tester, and testimony, then was closed with a post-test. There were several results obtained from the implementation of the community service activities, which were the increase in residents' knowledge about hypertension, the benefits of Clitoria ternatea L. flowers for health, and how to process Clitoria ternatea L. flowers into herbal drinks that are efficacious for health. In the processing into herbal drinks, the flower can be combined with other herbal ingredients to obtain other properties and a more delicious taste.